2017
DOI: 10.1016/j.ejvs.2017.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Late Dacron Patch Inflammatory Reaction after Carotid Endarterectomy

Abstract: Late wound complications after CEA may be related to inflammatory reaction of the Dacron patch rather than infection. Infection should be excluded first. Reconstruction with vein is effective. However, debridement with sternomastoid and omohyoid muscle covering of the patch may be considered in high risk patients after exclusion of infection with regular follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Previous histopathological analyses of explanted vascular grafts have demonstrated that the host cell response often determines the fate of the implanted material. Commercially available synthetic grafts can provoke inflammatory reactions, fail to integrate properly into the surrounding tissue, and can inhibit host neutrophil behavior leading to sustained bacterial infections (29)(30)(31). Chemically cross-linked, sterilized, or cryopreserved allografts and xenografts have also been shown to trigger inflammatory and immune responses and fail to appropriately recellularize (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Previous histopathological analyses of explanted vascular grafts have demonstrated that the host cell response often determines the fate of the implanted material. Commercially available synthetic grafts can provoke inflammatory reactions, fail to integrate properly into the surrounding tissue, and can inhibit host neutrophil behavior leading to sustained bacterial infections (29)(30)(31). Chemically cross-linked, sterilized, or cryopreserved allografts and xenografts have also been shown to trigger inflammatory and immune responses and fail to appropriately recellularize (32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…15 Additionally, late Dacron patch inflammatory complications in humans has been reported up to 7 years post-implantation. 16 Therefore, secondarily, a foreign body reaction could have developed from the Dacron cuff within the abdominal cavity, contributing to the transmural migration into the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding this disruptive paper, the available evidence from the literature would suggest that surgical exploration along with patch excision and debridement of all infected tissue combined with autologous revascularisation, remains the gold standard for the majority of patients with suspected patch infection. As shown in the studies by Alawy et al and Mann et al, 1,2 replacement with a prosthetic patch carries a high risk of re-infection and should be avoided. The same is true for carotid ligation, which is associated with a high risk of peri-operative stroke but may be necessary in rare cases of infection with highvirulence organisms.…”
mentioning
confidence: 94%
“…The same is true for carotid ligation, which is associated with a high risk of peri-operative stroke but may be necessary in rare cases of infection with highvirulence organisms. Finally, while we admit that insertion of a covered stent for a ruptured pseudoaneurysm, makes sense 1,3 , it should remain a bridge to delayed autogenous revascularisation.…”
mentioning
confidence: 96%
See 1 more Smart Citation